Modelling and Control of Mobile Manipulator - Mr. Ali Choucha; Mr. Fathi Madjour; RAHMANI Belkacem (UNIVERSITE Amar Telidji de Laghouat.FACULTE DE TECHNOLOGIE.DEPARTEMENT D’ELECTROTECHNIQUE, 2022)
The rising number of robot manipulators required to execute a job has necessitated the development of complex control algorithms. However, because the efficiency and stability of these schemes are the primary concerns, as a result, the focus has shifted away from developing accurate and precise kinematics and dynamics models. Such Models are the foundation of every control method since they give fundamental information. About the system's characteristics the youBot mobile manipulator from KUKA is a manipulator installed on a transportable platform designed for educational and research applications Because of its kinematics, the five (low)-DOF manipulator is an intriguing case study and in fact it’s difficult. Furthermore, the omnidirectional platform on which the manipulator is placed is an intriguing instance itself. The purpose of this thesis is to create a kinematic model for the KUKA youBot in two parts: a separated system (mobile platform model and a manipulator model) and combined system, then controlling the obtained models using MATLAB.
Option: Automatic and systems